Application of a fungicide system on tomato in open ground conditions in Primorsky Krai - I. A. Vanyushkina; N. A. Sinichenko; E. G. Kozar (Овощи России, 2023)
Relevance. Tomato is one of the most beloved and popular vegetables among Primorye residents. But in the monsoon climate, the Far Eastern Primorye has the most intense infectious background in Russia. The yield losses of tomato fruits from alternariosis annually amount to 30% or more. Losses from late blight on the background of epiphytotics in years with wet and cold summers, as observed in 2019, depending on the stability of the variety, can reach from 17 to 100%. Despite the fact that the development and use of biological means of control has recently been a priority, it is still too early to abandon chemical protection measures. High efficiency and versatility of the correctly selected scheme of application of fungicides, short processing time – all this gives a quick and reliable result in protecting tomato crops and reducing the harmfulness of the complex of diseases.Methodology. The research was carried out in 2019-2021 at the Primorsky Vegetable Experimental Station (PVES) – a branch of the Federal Scientific Vegetable Center in the monsoon climate of the coastal zone of Primorsky Krai. We studied the effect of chemical preparations Signum, Orvego and their tank mixture with igum + Orvego on the development of diseases, yield indicators and the structure of the tomato crop varieties Odyssey, and Fitilek. Agrotechnics of cultivation are generally accepted in Primorsky Krai for tomato culture.Results. Testing of chemical fungicides in the conditions of Primorsky Krai showed that the development of alternariasis, starting with the appearance of the first signs of damage in the first half of the growing season, effectively restrains the fungicide Signum, contributing to the preservation of the working leaf surface. It is advisable to use the tank mixture With igum + Orvego starting from the first or second decade of August, when a complex of phytopathogens develops on the leaf surface. The introduction of these two fungicides into the tank mixture leads to an increase in the biological and economic effectiveness of protective measures in the fight against alternariasis and late blight of tomatoes, compared with the standard fungicide Acrobat MC. Joint Signum Processing+Orvego, by reducing the intensity of disease development and the share of the non-commodity part of the crop, has a beneficial effect on the mass of commercial fruit and contributes to a more complete realization of the productive potential of Odyssey and Fitilek varieties.